The effect of alpha-melanocyte stimulating hormone on colonic inflammation in the rat - YEGEN, BERRAK; ERCAN, FERİHA (My University, 2000)
The effect of alpha-melanocyte stimulating hormone (alpha-MSH) on colonic inflammation in the rat. In this study, we investigated the effects of alpha-MSH administration on trinitrobenzene sulfonic acid-induced colitis and the role of nitric oxide and prostaglandins in this response. alpha-MSH treatment (25 microg/rat, intraperitoneally; twice daily for 3 days) reduced the colonic macroscopic lesions compared to untreated ones in both acute and chronic colitis groups. This effect was reversed by pretreatment with the nitric oxide donor, sodium NP (4 mg/kg, intravenously) or cyclooxygenase-1 selective antagonist indomethacin (5 mg/kg, subcutaneously) in the acute group and with the cyclooxygenase-2 selective antagonist nimesulide (3 mg/kg, subcutaneously) in the chronic group. alpha-MSH had no effect on colonic wet weight and myeloperoxidase activity compared to the untreated colitis group. However, protein oxidation was markedly elevated in the alpha-MSH-treated group compared to untreated ones. Nitroprusside and indomethacin reversed the effect of alpha-MSH on macroscopic lesions in the acute groups, whereas nimesulide showed a similar effect in the chronic group. In conclusion, the results of our study show a protective role of alpha-MSH on colonic lesions which partially involves nitric oxide and prostaglandins.
Keywords: Female; Animals; Male; Rats; Antihypertensive Agents; Colitis; Signal Transduction; Free Radical Scavengers; Trinitrobenzenesulfonic Acid; Nitric Oxide; Rats, Sprague-Dawley; Anti-Inflammatory Agents, Non-Steroidal; Indomethacin; Nitric Oxide Donors; Nitroprusside; Sulfonamides; alpha-MSH; Membrane Proteins; Prostaglandin-Endoperoxide Synthases; Isoenzymes; Cyclooxygenase 1; Prostaglandins